Elipsis Posposisi Bahasa Jepang dalam Komik Akira Karya Hiromasa Okushima - Mhd. Pujiono; Abdul Gapur; Taulia Taulia (Ranah: Jurnal Kajian Bahasa, 2023)
In the context of everyday conversation, there is a phenomenon of ellipsis or disappearance in Japanese. One element of the word class that experiences ellipsis is postposition, which is a word class that plays an essential role in clarifying the function of a word in a sentence. This study examines the postpositional ellipsis in the Japanese conversation's comic Akira No. 2 by Hiromasa Okushima. The aim is to explain the form and process of the occurrence of Japanese postpositional ellipsis in conversation. This study uses a qualitative approach with a descriptive method. The data are conversational sentences with a postpositional ellipsis originating from the comic Akira No. 2 by Hiromasa Okushima Volume 1, chapter 1. Reading and note-taking techniques are used in data collection. The results indicate that there are postposition ellipsis wa (は), ga (が), no (の), e (へ), ni (に), o (を), and ka (か) occur in conversations between characters. The process of postposition ellipsis is influenced by the context of the conversation and occurs in character dialogue in comics in informal situations. Proposition ellipsis does not change the information or message in the sentence so that the interlocutor still understands the speaker's intent. AbstrakDalam konteks percakapan sehari-hari, terdapat fenomena elipsis atau pelesapan dalam bahasa Jepang. Salah satu unsur kelas kata yang mengalami elipsis adalah posposisi, yakni kelas kata yang berperan penting dalam memperjelas fungsi sebuah kata dalam kalimat. Dalam penelitian ini dikaji elipsis posposisi yang terjadi dalam percakapan bahasa Jepang dalam komik Akira No. 2 karya Hiromasa Okushima. Tujuannya adalah menjelaskan bentuk dan proses terjadinya elipsis posposisi bahasa Jepang pada percakapan.  Penelitian ini menggunakan pendekatan kualitatif dengan metode deskriptif. Data adalah kalimat percakapan yang mengalami elipsis posposisi yang bersumber dari komik Akira No. 2 karya Hiromasa Okushima Volume 1 chapter 1. Digunakan teknik simak dan catat dalam pengumpulan data. Hasil penelitian ini menunjukkan terdapat elipsis posposisi wa (は), ga (が), no (の), e (へ), ni (に), o (を) dan ka (か) terjadi dalam percakapan antarkarakter. Proses elipsis posposisi dipengaruhi oleh konteks percakapan dan terjadi pada dialog karakter dalam komik dalam situasi tidak formal. Elipsis posposisi tidak mengubah informasi atau pesan di dalam kalimat sehingga lawan bicara tetap mengerti maksud pembicara.